Plant microtechnique and microscopy - Ruzin, Steven E. (Oxford University Press, 1999)
Plant microtechnique has generated renewed interest in recent years, due in part to the need for molecular biologists to visualize a gene or gene product in the context of the whole plant. Plant Microtechnique and Microscopy offers uniquely in-depth coverage of this reinvigorated field. Thoroughly covering classical aspects of microscope slide preparation, it goes a step beyond all other available manuals by also documenting the theory and practice of modern applications.